Influence of Therapist Attachment Style on the Working Alliance in Individual Psychotherapy: A Systematic Review and Meta-Analysis - Marín Cavestany, María; De la Cruz, María Ángeles; Durán, Juan I.; Stiles, Bryan J.; Lahera, Guillermo; Andrade González, Nelson (Wiley, 2025)
Introduction: Attachment style and working alliance are two fundamental variables in psychotherapy. This systematic review aims to provide data on the relationship between therapist attachment and alliance in psychotherapy, updating a previous review and providing a quantitative synthesis (meta-analysis). Method: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Statement recommendations were followed. The databases PsycINFO, PubMed and Web of Science were searched from June 1, 2016, to May 30, 2024, sup plemented by a manual search. A regulated study selection process was performed, followed by data extraction and risk of bias assessment. A qualitative and quantitative analysis of the included studies was performed. Results: Nine studies were selected for the systematic review that included 354 patients and 741 mental health professionals. In five studies, different types of attachment (secure, anxious and avoidant) were related to the alliance. In addition, this relation ship was partially mediated by therapeutic optimism, role security, therapeutic commitment or emotional regulation strategy. Of the 23 articles selected from both systematic reviews, 12 studies were included in the meta-analysis. A systematic correlation between anxious attachment style and the alliance was found only when the assessment of the alliance was performed by ther apists (r=¿0.31). Conclusions: There is evidence that therapist attachment may influence the formation and maintenance of a higher-quality working alliance. However, further studies with more precise measures of both constructs are needed to better understand this relationship and its clinical implications.
Keywords: anxious attachment | avoidant attachment | psychotherapy | secure attachment | working alliance